2021
DOI: 10.21203/rs.3.rs-21247/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predicting the Incidence of COVID-19 Using Data Mining

Abstract: Background: The high prevalence of COVID-19 has made it a new pandemic. Predicting both its prevalence and incidence throughout the world is crucial to help health professionals make key decisions. In this study, we aim to predict the incidence of COVID-19 within a two-week period to better manage the disease. Methods: The COVID-19 datasets provided by Johns Hopkins University, contain information on COVID-19 cases in different geographic regions since January 22 and are updated daily. Data from 252 such regio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The highest accuracy in the present study was reported at 99.14% using the KNN2 algorithm. The accuracy of the regression model used in the study conducted by Ahouz et al [18] was obtained at 83% and in the study conducted by Li et al [21], it was obtained at 0.8698 with the SVM (Linear kernel) model. In the study conducted by Ahouz et al [18], 17136 records and 4 variables (latitude, longitude, history, and background) were analyzed.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…The highest accuracy in the present study was reported at 99.14% using the KNN2 algorithm. The accuracy of the regression model used in the study conducted by Ahouz et al [18] was obtained at 83% and in the study conducted by Li et al [21], it was obtained at 0.8698 with the SVM (Linear kernel) model. In the study conducted by Ahouz et al [18], 17136 records and 4 variables (latitude, longitude, history, and background) were analyzed.…”
Section: Discussionmentioning
confidence: 90%
“…The accuracy of the regression model used in the study conducted by Ahouz et al [18] was obtained at 83% and in the study conducted by Li et al [21], it was obtained at 0.8698 with the SVM (Linear kernel) model. In the study conducted by Ahouz et al [18], 17136 records and 4 variables (latitude, longitude, history, and background) were analyzed. Li et al [21] also identified stress symptoms in people due to the COVID-19 outbreak using data mining.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations